2001
DOI: 10.1046/j.1365-294x.2001.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrilinear phylogeography of Atlantic salmon (Salmo salar L.) in Europe and postglacial colonization of the Baltic Sea area

Abstract: Sixty-four samples from 46 salmon populations totalling 2369 specimens were used for polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis of the mitochondrial ND1 region. The final analyses included 3095 specimens from 60 populations in Northern Europe. A subsample was analysed by RFLP of ND3/4/5/6. Representative RFLP haplotypes from different parts of the distribution area were sequenced and the phylogeny of European haplotypes and their relations to the North American linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
183
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(202 citation statements)
references
References 40 publications
(91 reference statements)
18
183
0
1
Order By: Relevance
“…The network is most parsimoniously linked to the European haplotype group through haplotype i; there are only two main salmon lineages -North American and European (King et al, 2000;Nilsson et al, 2001). Five mutations (0.7% divergence) in the sequenced regions separate the two haplotypes based on the data of Hurst et al (1999;GenBank U12143); six or more mutations separate this European variant from the other haplotypes detected in the present study.…”
Section: Diversity Analysismentioning
confidence: 68%
See 3 more Smart Citations
“…The network is most parsimoniously linked to the European haplotype group through haplotype i; there are only two main salmon lineages -North American and European (King et al, 2000;Nilsson et al, 2001). Five mutations (0.7% divergence) in the sequenced regions separate the two haplotypes based on the data of Hurst et al (1999;GenBank U12143); six or more mutations separate this European variant from the other haplotypes detected in the present study.…”
Section: Diversity Analysismentioning
confidence: 68%
“…Only two variable sites were reported for the same part of the gene in 32 salmon derived from a much larger geographical area spanning both Baltic and nonBaltic phylogenetic groups in Europe (Nilsson et al, 2001). Haplotype (h) and nucleotide diversity ( ) observed for Baltic and non-Baltic salmon for the gene region studied were 0.3282 (±0.0768) and 0.000475, and 0.5362 (±0.0904) and 0.000975, respectively (based on data in Nilsson et al, 2001). Average Bay of Fundy values for h and (Table 1) are similar to the more diverse non-Baltic European salmon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In seagrass meadows, it has been shown that stands with less genetic variation are less productive, have lower diversity of associated flora and fauna, and are more susceptible toward extreme climate conditions (Reusch et al 2005). Direct effects on ecosystem services (fisheries harvest) were strongly related to the existence of genetically distinct populations of Sockeye salmon in the Pacific (Schindler et al 2010), and it seems possible that Baltic Sea salmon fishery and possibly other fisheries like the cod fishery may be benefitting in a similar way owing to genetically distinct local stocks (Nilsson et al 2001;Sterner 2007).…”
Section: Effects Of Genetic Variation On Ecosystem Functionmentioning
confidence: 99%